2018
DOI: 10.1016/j.brainresbull.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vertical sleeve gastrectomy on alcohol consumption and preferences in dietary obese rats and mice: A plausible role for altered ghrelin signaling

Abstract: Vertical sleeve gastrectomy (VSG) and Roux-en-Y gastric bypass (RYGB) are the most common surgical options for the treatment of obesity and metabolic disorder. Whereas RYGB may result in greater and more durable weight loss, recent clinical and pre-clinical studies in rats have raised concerns that RYGB surgery may increase risk for alcohol use disorder (AUD). In contrast, recent clinical reports suggest a lesser risk for AUD following VSG, although no preclinical studies have been done to confirm that. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 108 publications
2
11
0
Order By: Relevance
“…Our data indicate that VSG reduced intake of alcohol at low concentration and that this phenomenon is diminished as the concentration of alcohol is escalated. These data are in agreement with a recent preclinical study that found reduced alcohol intake after VSG surgery ( 26 ). However, in that study, VSG rats and mice consumed significantly less alcohol at all concentrations tested.…”
Section: Discussionsupporting
confidence: 93%
“…Our data indicate that VSG reduced intake of alcohol at low concentration and that this phenomenon is diminished as the concentration of alcohol is escalated. These data are in agreement with a recent preclinical study that found reduced alcohol intake after VSG surgery ( 26 ). However, in that study, VSG rats and mice consumed significantly less alcohol at all concentrations tested.…”
Section: Discussionsupporting
confidence: 93%
“…In other words, RYGB was more invasive to the vagal innervation of the gastrointestinal tract than SG. Furthermore, these procedural differences between SG and RYGB are found to alter food and alcohol consumption, based on evidence from recent animal studies . Here, we propose that these differences can also explain the differential olfactory outcomes following RYGB and SG.…”
Section: Resultsmentioning
confidence: 62%
“…Vertical sleeve gastrectomy is another common surgical option for the treatment of obesity. Rats that underwent this surgery underwent the removal of the ghrelin producing part of the stomach and showed a decreased preference for alcohol than control subjects (Orellana, Jamis, Horvath, & Hajnal, ). There has been other studies comparing different bariatric techniques that found increased drinking in RYGB groups but not gastric banding (Conason et al, ; King et al, ; Suzuki, Haimovici, & Chang, ; Svensson et al, ).…”
Section: Discussionmentioning
confidence: 99%